Pengaruh Penggunaan Media Dakon Matematika terhadap Hasil Belajar Siswa Kelas Tinggi SD di Kabupaten Gowa - Risnawati Risnawati; Ari Wibowo; Bahar Bahar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
This study aims to determine the use of dakon media on the learning outcomes of high school students in Gowa Regency then to find out the significant effect of using media dakon on the mathematics learning outcomes of high school students in Gowa Regency. The approach used is a quantitative approach. The type of research conducted is True-Experimental Design, which is a sample used for experiments and control groups taken randomly from certain populations. The research variables consist of two, namely the dakon Media as the independent variable (X) and Learning Outcomes as the dependent variable (Y). The research design used in this study was the Design Matching Pretest-Posttest Control Group Design. random sample research (Therandomized pretest-posttest control grouf design. The population in this study were all high school students in Gowa Regency, totaling 836 elementary schools. Data analysis technique used was to test hypotheses using t-test with independent samples test t test The results of the study showed that the learning process using the mathematics media was effective, it was seen that there was a significant influence of the use of mathematics media media to the mathematics learning outcomes of high school students in Gowa Regency.